جدلية العلاقة بين العقل والنقل عند عبد الباري الندوي - باي, أحمد عامر (University of Eloued جامعة الوادي, 2017)
يهدف هذا المقال إلى معالجة إشكالية العلاقة بين العقل والنقل، التي كانت وما تزال محل تجاذب وخلاف واسع بين المفكرين والفلاسفة، وممّن تناول الموضوع بالدراسة الشيخ عبد الباري الندوي استجابةً لتحديات عصره، بالوقوف بحزمٍ أمام التيارات الوافدة من باب العقلانية والافتتان بالنتائج العلمية العملاقة في القرنين الماضيين، كما عارض الانسياق وراء التيارات الفلسفية المختلفة التي أقحمت العقل في المجال الميتافيزيقي. ومقالي هذا يسلط الضوء على جهده في تحديد العلاقة بين العقل والنقل، والمجالات المعرفية لكليهما، فقد استطاع الندوي أن يوضح وهم الصراع بين العلم والدين، ويبين طبيعة العلاقة بين المذاهب الفلسفية والكلامية المختلفة والدين، ليخلص في الأخير إلى تحديد طبيعة علاقة العقل بالنقل، والمجال المعرفي لكل منهما. Abstract This article used to discuss the question of the relationship between intellect and revelation according to the scholar Abdul Bari Nadwi who dealt with that subject , in terms of the huge dispute between philosophers and thinkers .it is a significant topic that Abdul Bari Nadwi is concerned about , he responded to the challenges of his current time, in order to stand against of the modern trends which was influenced by rationality and scientific results that have been achieved in the last two centuries, he was totally oppose putting intellect in metaphysical field. My article stresses the importance of defining the relationship between the intellect and the revelation and both of their fields . Nadwi concluded that there is conflict between science and religion, he shows nature of the relationship between all thought schools and the religion , at the end , he achieved that each one of them has its field
The Dialectic relationship between intellect and revelation according to Abdelbari Nadwi
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: العقل - النقل - الدين - الفلسفة – العلم - علم الكلام; intellect, revelation, religion, philosophy, art of discussion.